Pendidikan Politik Bagi Pemilih Pemula di SMAN 1 Meureubo Kabupaten Aceh Barat - Vellayati Hajad; Ikhsan Ikhsan (Universitas Teuku Umar, 2019)
Political education is a very important thing to do in increasing the participation of first-time voters. First time voters are those aged between 17 to 24 years, but in this service the first time voters in question are the students of SMAN 1 Meureubo who are sitting in the third grade of high school and already have the right to vote. The method used in this service is by lecturing, sharing sessions, and simulations with video and practice selection procedures. The results of devotion show that the political participation of novice voters in elections is strongly influenced by the level of knowledge, understanding and literacy (political literacy) possessed by novice voters. Before the results of the pre-test activities of students' knowledge 57.25 and after getting political education through lecture methods, sharing sessions, and video simulations and practices the average score rose to 70.25. In conclusion, there was an increase in students' knowledge regarding political participation.